Diversity of myxozoans parasitizing the catfish Rhamdia quelen (Siluriformes: Heptapteridae), in southeastern Brazil, based on morphological and molecular evidence - Diego Henrique Mirandola Dias Vieira; Rodrigo Bravin Narciso; Reinaldo José da Silva (Scientific Reports, 2022)
Abstract Rhamdia quelen is a commercially important fish in South America. During the survey of myxozoan infections in fishes from Pardo River, Paranapanema River basin, São Paulo State, Brazil, we describe three new species of Henneguya found parasitizing gills of R. quelen: Henneguya bagre n. sp., Henneguya breviscauda n. sp and Henneguya novaerae n. sp. The descriptions were based on myxospores morphology and small subunit ribosomal DNA partial sequences. Phylogenetic analysis showed a clade formed by species that parasitize Siluriformes, with Henneguya jundiai as a sister species of Henneguya bagre n. sp., Henneguya breviscauda n. sp and Henneguya novaerae n. sp. Our study indicates that the parasites infecting R. quelen belong to a lineage of myxozoans infecting Heptapteridae fishes. Using molecular and morphological characterization, the species were identified as new species for the genus Henneguya. Based on our analysis we recommend monitoring the presence of these parasites in farmed fishes, to analyze possible pathologies caused by them.